Akta Peralihan Harta Pailit Berupa Benda Tetap Yang Dijual Tanpa Lelang Oleh Kurator - M. Yasser Al Mursyid (Officium Notarium, 2021)
This research examines the deed of transfer of bankrupt assets in the form of fixed objects which are sold without auction by the Curator. The problem formulated in this research is first, why there is a transfer of bankrupt assets in the form of fixed objects that are sold without an auction by the Curator. Second, how is the authority and responsibility of PPAT for the deed of transfer of bankrupt assets in the form of fixed objects that are sold without an auction by the Curator. This research is normative with a statutory and a conceptual approaches. The results of the study conclude that first, that there are various problems that arise from the existence of an auction selling mechanism that disrupts the independence of the curator so that the curator prefers to sell under hands. Second, PPAT's responsibility when associated with his profession adheres to the principle of error responsibility so that in making an authentic deed, PPAT must be responsible if there is an error or violation of the deed he made Key Word: Bankruptcy Law, PPAT, transfer of deedAbstrakPenelitian ini meneliti tentang akta peralihan harta pailit berupa benda tetap yang dijual tanpa lelang oleh Kurator. Masalah yang dirumuskan dalam penelitian ini pertama, mengapa terjadi peralihan harta pailit berupa benda tetap yang dijual tanpa lelang oleh Kurator. Kedua, bagaimana wewenang dan tanggung jawab PPAT atas akta peralihan harta pailit berupa benda tetap yang dijual tanpa lelang oleh Kurator. Penelitian ini secara normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menyimpulkan, pertama, berbagai masalah yang timbul dari adanya mekanisme penjualan secara lelang yang menyebabkan terganggunya independensi Kurator sehingga Kurator lebih memilih penjualan secara di bawah tangan. Kedua, Tanggungjawab PPAT apabila dikaitkan dengan profesinya menganut prinsip tanggungjawab kesalahan sehingga dalam pembuatan akta otentik, PPAT harus bertanggungjawab apabila terjadi kesalahan atau pelanggaran terhadap akta yang dibuatnya.Kata Kunci: PPAT, Akta Peralihan, Hukum Kepailitan